2022
DOI: 10.1039/d2py01153k
|View full text |Cite
|
Sign up to set email alerts
|

Ring size-reactivity relationship in radical ring-opening copolymerisation of thionolactones with vinyl pivalate

Abstract: The radical ring-opening copolymerisation (rROcoP) of unsubstituted thionolactones of different ring sizes, namely γ-thionobutyrolactone (TBL), δ-thionovalerolactone (TVL), ε-thionocaprolactone (TCL) and ω-thionopentadecalactone (TPDL), with vinyl pivalate has been mechanistically investigated. The...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…General Procedure for the Preparation of Poly(TL-co-VP). Based on previous procedures, 21 TL and VP were mixed together with 0.5 mol % VAZO-88 relative to comonomers. The solution was transferred into a Carius tube that was sealed under vacuum after degassing by three freeze−pump−thaw cycles.…”
Section: Synthesis Of 1-(octylsulfanyl)ethan-1-one Tementioning
confidence: 99%
See 3 more Smart Citations
“…General Procedure for the Preparation of Poly(TL-co-VP). Based on previous procedures, 21 TL and VP were mixed together with 0.5 mol % VAZO-88 relative to comonomers. The solution was transferred into a Carius tube that was sealed under vacuum after degassing by three freeze−pump−thaw cycles.…”
Section: Synthesis Of 1-(octylsulfanyl)ethan-1-one Tementioning
confidence: 99%
“…■ RESULTS AND DISCUSSION TBL, TVL, and TCL, which were recently reported 21 for the preparation of copolymers with VP, were used in this study. Copolymers of TL with VP were prepared with different fractions of incorporated TL and different ratios between TLs incorporated in thioester or S,O-thioketal forms (Scheme 4).…”
Section: Synthesis Of 1-(octylsulfanyl)ethan-1-one Tementioning
confidence: 99%
See 2 more Smart Citations
“…The polymerizations typically required very low temperatures (−78 to −120 °C). Very recently, a few reports on radical polymerizations of cyclic thiocarbonyl compounds indicated that some thionolactones were incorporated into a polymer as a mixture of ring-opened and cyclic structures with and without β-scission, respectively, which depended on the monomer structure and the polymerization conditions. …”
mentioning
confidence: 99%